2014
DOI: 10.1289/ehp.1206323
|View full text |Cite
|
Sign up to set email alerts
|

Domain-Specific Effects of Prenatal Exposure to PCBs, Mercury, and Lead on Infant Cognition: Results from the Environmental Contaminants and Child Development Study in Nunavik

Abstract: Background: Polychlorinated biphenyls (PCBs), methylmercury (MeHg), and lead (Pb) are environmental contaminants known for their adverse effects on cognitive development.Objectives: In this study we examined the effects of prenatal exposure to PCBs, MeHg, and Pb on cognitive development in a sample of Inuit infants from Arctic Québec.Methods: Mothers were recruited at local prenatal clinics. PCBs, mercury (Hg), Pb, and two seafood nutrients—docosahexaenoic acid (DHA) and selenium (Se)—were measured in umbilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 66 publications
4
71
0
2
Order By: Relevance
“…Of 20 previous studies using the BSID (Davidson et al 1995(Davidson et al , 2008Jedrychowski et al 2006Jedrychowski et al , 2007Lederman et al 2008;Plusquellec et al 2010;Stokes-Riner et al 2011;Llop et al 2012;Watson et al 2012;Valent et al 2013;Boucher et al 2014;Hsi et al 2014;Strain et al 2015;Marques et al 2015Marques et al , 2016aRothenberg et al 2016;Julvez et al 2016;Prpić et al 2017), 11 reported adverse effects of methylmercury on the PDI, and three observed such effects on the MDI; that is, these rates of 11/20 and 3/20 differed significantly (Fisher exact test, P = 0.019). Thus, psychomotor development appeared to be more susceptible to methylmercury than mental development.…”
Section: Discussionmentioning
confidence: 87%
“…Of 20 previous studies using the BSID (Davidson et al 1995(Davidson et al , 2008Jedrychowski et al 2006Jedrychowski et al , 2007Lederman et al 2008;Plusquellec et al 2010;Stokes-Riner et al 2011;Llop et al 2012;Watson et al 2012;Valent et al 2013;Boucher et al 2014;Hsi et al 2014;Strain et al 2015;Marques et al 2015Marques et al , 2016aRothenberg et al 2016;Julvez et al 2016;Prpić et al 2017), 11 reported adverse effects of methylmercury on the PDI, and three observed such effects on the MDI; that is, these rates of 11/20 and 3/20 differed significantly (Fisher exact test, P = 0.019). Thus, psychomotor development appeared to be more susceptible to methylmercury than mental development.…”
Section: Discussionmentioning
confidence: 87%
“…The psychomotor development index (PDI) assesses fine and gross motor skills, while the mental development index (MDI) assesses cognition and language, and thus is relevant to this discussion. Cohorts in North Carolina, the Netherlands, Quebec, and Duisburg, Germany were assessed at multiple ages using the BSID or BSID-II, and no associations between MDI scores and either prenatal or postnatal PCB exposure were observed (Gladen et al, 1988; Gladen & Rogan, 1991; Koopman-Esseboom et al, 1996; Boucher et al, 2014; Wilhelm at al., 2008). In contrast, one study in Dusseldorf, Germany found a negative correlation between perinatal PCB exposure and MDI scores (Winneke et al, 1998; Walkowiak et al, 2001).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Besides methylmercury, deficits in cognitive function were also attributed to perinatal exposure to lead and PCBs; which can alone or in mixture act as neurotoxins. For instance lead, even at low doses, impairs cognitive functions in childhood such as attention and intellectual function [54]. In a cohort study, maternal consumption of PCB-contaminated fish was associated with poorer visual recognition memory in babies at 7 months postpartum [55].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a recent study, it has been shown that prenatal exposure to PCBs, mercury, and lead resulted in impaired cognitive development in Inuit infants from Arctic Québec, assessed at 6.5 and 11 months. It has been postulated that each type of contaminants may have its own "behavioral signature", with PCBs being associated with visual recognition memory, MeHg with working memory and an early precursor of executive function, and lead with processing speed [54].…”
Section: Accepted Manuscriptmentioning
confidence: 99%